Temperature as a potential regulator for Ebola virus replication in primary cells from Mops condylurus - Bokelmann, Marcel; Riesle-Sbarbaro, Silke A.; Lander, Angelika; Wahlbrink, Annette; Groschup, Martin H.; Balkema-Buschmann, Anne; Couacy-Hymann, Emmanuel; Prescott, Joseph; Kurth, Andreas (Frontiers in Virology, 2024)
IntroductionFor more than 40 years, outbreaks of ebolavirus disease have been documented, but the natural reservoir(s) of ebolaviruses remain unknown. However, recent studies provide evidence that the Angolan free-tailed bat (Mops condylurus), an insectivorous bat belonging to the family Molossidae, is a likely ebolavirus reservoir. Being a heterothermic species, M. condylurus bats are highly tolerant to variations in ambient temperatures, and therefore are capable of living under a broad range of climatic and environmental conditions by using adaptive thermoregulation. Body core temperatures as low as 12.0°C have been measured during winter, while increased body temperatures were observed in their hot roosts or during flight, reaching temperatures typical of fever in most other mammalian species.MethodsHere, we investigated the impact of temperature fluctuations between 27°C and 42°C on Ebola virus (EBOV) survival and replication kinetics in cells from M. condylurus using qRT-PCR.ResultsWe found that primary cells derived from M. condylurus, similar to the bats in their natural environment, were highly tolerant to temperature variations. EBOV replication was temperature-dependent, showing a strong reduction of replication efficiency at low temperature.DiscussionWe therefore conclude, that heterothermy might be involved in balancing the level of EBOV replication and thereby be a key factor for tolerating EBOV infections in vivo.